Exploring How Gender Shapes Workers’ Perceptions of Micro-Retirement in Yogyakarta - Putri, Agustin Andhika (The Future of Education Journal, 2025)
Micro-retirement is a phenomenon currently prevalent in Indonesia. Micro-retirement, or early retirement, is a phenomenon where individual workers, both men and women, decide to take a break from work for a few months or even years. The purpose of this study was to examine whether male and female gender correlation workers' perceptions of micro-retirement decisions. The sample size for this study was 59 people who were still employed. The sample characteristics were employees who were still working, both men and women, working in Indonesia. Researchers distributed questionnaires to the sample to be completed online. This study used a quantitative method by conducting a chi-square correlation test. This method was used to examine whether gender had a significant influence on the perception of micro-retirement among Indonesian employees. If the sig. <0.05, then the null hypothesis is rejected and Hypothesis a is accepted. The result of the correlation test in this study was 0.862. Because the result was more than 0.05, the null hypothesis was accepted. This means there is no relationship between gender and the perception of micro-retirement. This research demonstrates that both men and women can have micro-retirement perceptions. However, gender is not the determining factor in employees' perceptions of early retirement. Several factors influence individuals' perceptions of micro-retirement, including health, work stress, and family.